2021
DOI: 10.3399/bjgp.2021.0193
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physician empathy on patient outcomes: a gender analysis

Abstract: Background: Empathy in primary care settings has been linked to improved health outcomes. However, the operationalisation of empathy differs between studies, and no study concurrently compared affective, cognitive, and behavioural components of empathy regarding patient outcomes. Moreover, it is unclear how gender interacts with the studied dimensions. Aim: To examine the relationship between several empathy dimensions and patient-reported satisfaction, consultation’s quality and trust in physician, and to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…41 Physician gender should also be considered, as a recent study showed that verbal empathy statements were linked to higher patient satisfaction only when the physician was male. 42 We did not find any differences in the ESr according to the nature of empathy. Only the studies that comprised at least the emotional process of empathy (i.e., a genuine interest in and a full understanding of the patient, genuine care and compassion) were included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…41 Physician gender should also be considered, as a recent study showed that verbal empathy statements were linked to higher patient satisfaction only when the physician was male. 42 We did not find any differences in the ESr according to the nature of empathy. Only the studies that comprised at least the emotional process of empathy (i.e., a genuine interest in and a full understanding of the patient, genuine care and compassion) were included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 49%
“…In this regard, artificial intelligence may be a precious tool in the future to code this iterative process along with non‐verbal (e.g., prosodic features) and physiological reactions (e.g., cortisol secretion) of both clinicians and patients 41 . Physician gender should also be considered, as a recent study showed that verbal empathy statements were linked to higher patient satisfaction only when the physician was male 42 …”
Section: Discussionmentioning
confidence: 99%
“…We also found that reflective capacity mediated the relationship between reflective writing and perceived better patient care. While there is evidence supporting the role of medical humanities in fostering empathy 10,17,18 and the association between empathy and improved patient care, [33][34][35] there is less research into whether the use of medical humanities directly impacts patient care, though some theories as to how this might be achieved have been proposed. Building on the work of Charon, 14 Lapite proposed that by fostering empathy for patients, medical humanities help to improve the clinicianpatient relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Other foundational helping competencies include rapport building, the demonstration of empathy, using culturally or age-appropriate terminology and concepts for distress, and ensuring communication of hope. Competent use in foundational helping by health and care workers improves outcomes for people accessing different fields of health services, ranging from surgery to pain clinics (Kohrt et al, 2015 ; Hojat, 2016 ; Golshan et al, 2019 ; Walsh et al, 2019 ; Surchat et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%